Analysis of Creative Thinking Ability in Geometry Learning with the Problem Based Learning (PBL) Model - Hendri Handoko; St. Budi Waluya; Rochmad Rochmad; Sugiman Sugiman (International Conference on Science, Education, and Technology, 2022)
Abstrak. This study aims to analyze and describe the ability to think creatively in geometry learning with the Problem Based Learning (PBL) model. The type of research used is descriptive-qualitative with research subjects 6 students selected by purposive sampling technique consisting of 2 students representing the group with high cognitive abilities, hereinafter referred to as the upper group with codes S-01 and S-02, 2 students representing the group with moderate cognitive ability, hereinafter referred to as the middle group with codes S-03 and S-04 and 2 students representing the group with low cognitive abilities, hereinafter referred to as the lower group with codes S-05 and S-06. The data collection techniques used were interviews, observation, document review, questionnaires and creative thinking ability test questions. There are five indicators of creative thinking skills analyzed, including: fluency, flexibility, originality, elaboration and evaluation. The results showed that the upper group met all indicators of the ability to think creatively at the level of lack of external relations, in the middle group 1 student met all indicators of the ability to think creatively at the level of lack of external relations, while the other 1 student did not meet the indicators of elaboration at the level of lack of internal relations and the lower group did not meet the elaboration and evaluation indicators at the level of lack-mixed relations.